2022
DOI: 10.1063/5.0096568
|View full text |Cite
|
Sign up to set email alerts
|

An exact tunneling model and its application to transmission and reflection delay times

Abstract: Electron emission into a nanogap is not instantaneous, which presents a difficulty in simulating ultra-fast behavior using particle models. A method of approximating the transmission and reflection delay (TARD) times of a wave packet interacting with barriers described by a delta function, a metal–insulator–metal (MIM, rectangular) barrier, and a Fowler Nordheim (FN, triangular) barrier is given and has application to simulation. It is based on the superposition of a finite number of exact basis states obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In this paper, we have used simple, analytical examples to demonstrate the correspondence between quantum mechanics and electromagnetism with the intent of establishing a framework for the verification and vali-dation of our previously developed atomistic emission models 18,[24][25][26][27] . Beginning with the frequency-dependent EM S-parameters which can either be calculated using HFSS or obtained through laboratory measurement, the frequency-dependent refractive index vector of a wire array medium was calculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we have used simple, analytical examples to demonstrate the correspondence between quantum mechanics and electromagnetism with the intent of establishing a framework for the verification and vali-dation of our previously developed atomistic emission models 18,[24][25][26][27] . Beginning with the frequency-dependent EM S-parameters which can either be calculated using HFSS or obtained through laboratory measurement, the frequency-dependent refractive index vector of a wire array medium was calculated.…”
Section: Discussionmentioning
confidence: 99%
“…The McColl-Hartman effect, which characterizes tunneling delay as a function of barrier width, was re-formulated using the Gamow factor, which is a function of barrier shape and incident energy as well as barrier width. Next, an exact trajectory method based on the Schrödinger equation 27 was developed to handle systems that are difficult to simulate using the Wigner approach, such as the rectangular and Fowler-Nordheim barriers. The approaches described here model both above and below barrier emis-sion and delays on an atomistic level, yet the trajectorybased nature of these approaches enables statistical modeling of emission on the mesoscale and generates output that can be used to inform higher-order material and device models.…”
Section: Introductionmentioning
confidence: 99%
“…incident on the barrier from the z < 0 region to the right. Where V0 and L are all greater than zero, V0 and L are the height and width of the triangular barrier respectively [17,18].…”
Section: Phase Time and Dwell Timementioning
confidence: 99%
“…[48] A recent study of the Harman effect through comparisons of tunneling in square and TBs can be found in Refs. [49,50]. Here we mainly compare the phase, dwell and Larmor times for a particle tunneling through a pair of MS ETBs, namely the positive-slope exact triangular barrier (PETB) and the negative-slope exact triangular barrier (NETB).…”
Section: Introductionmentioning
confidence: 99%